Evaluation of maternal mortality and their factors in GMCH, Aurangabad, India - Bharaswadkar, Ganesh Balasaheb; Kurtadikar, Murlidhar L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Analysing the factors related to maternal mortality is very important as they reflect the socioeconomic status and health care facility availabilities of the country. This study is aimed to analyse the epidemiological aspects and different causes of maternal death and evaluation of preventable factors and unavoidable factors if any causing maternal death. Methods: The retrospective study was carried out at GMCH, Aurangabad during the period from February 2002 to January 2004. All the data related to epidemiological factors and causes of maternal mortality was recorded and analyzed. Results: There were 33 maternal deaths during the study period. The mean maternal mortality rate was 211 per 1,00,000 total births. Maximum maternal deaths were reported at the age group of 26-30 years (36.1%), in primiparous women (46.8%) and from rural areas (78.38%). Most of the deaths (37.5%) were reported within first 24 hours of hospital admission at postpartum stage (87.5%). 84.37% of maternal deaths were due to direct causes. And toxemia of pregnancy (39.5%) was major direct cause. Anaemia and infective hepatitis constitutes for 9.3% each for the indirect causes maternal death. Conclusion: Most maternal deaths can be preventable by multidisciplinary approaches involving mass community education, improving sanitation, early referrals to tertiary care centres and by providing health care facilities in rural areas.